Evaluating Boston Harbor Cleanup: An Ecosystem Valuation Approach - Jin, Di; Watson, Chris; Kite-Powell, Hauke; Kirshen, Paul (Frontiers in Marine Science, 2018)
In this study, we develop an economic evaluation of the Boston Harbor Cleanup, a court-mandated action started in 1986, through a comparison of cleanup costs and relevant ecosystem service values. Our results suggest that the ecosystems in the study area provide services to society with a capitalized value ranging from $30 to $100 billion. The $4.7 billion cost of the Boston Harbor Cleanup is about 5%-16% of the total asset value of ecosystem services. Although it is not clear what fraction of the ecosystem value is due to the cleanup, our results suggest that the cost of the cleanup may be justified by our high- or midpoint-estimates of the value of ecosystem services.